2000
DOI: 10.1016/s1388-9842(00)80247-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biventricular pacing on mortality in a randomized crossover study of patients with heart failure and ventricular arrhythmias

Abstract: Conclusion:The physiological immune response to exercise is diminished in CHF patients who also exhibit significant catabolic/anabolic imbalance. This finding supports the concept that CHF presents a complex clinical syndrome with alterations in metabolic and immunological pathways and that a reduced exercise capacity may be caused also by more peripherally rather than central, cardiac abnormalities. P106/9931Skeletal muscle atrophy and decreased muscle strength correlate with cytokine activation in chronic he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 0 publications
3
31
0
4
Order By: Relevance
“…20,21,24,26,27 Seven trials compared cardiac resynchronization therapy and an implantable defibrillator (n = 2902) with an implantable defibrillator (n = 2281). 14,19,22,23,25,28,29 The length of follow-up ranged from 3 to 40 months. Five studies had a follow-up of 12 months or less.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…20,21,24,26,27 Seven trials compared cardiac resynchronization therapy and an implantable defibrillator (n = 2902) with an implantable defibrillator (n = 2281). 14,19,22,23,25,28,29 The length of follow-up ranged from 3 to 40 months. Five studies had a follow-up of 12 months or less.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of bias was often low except for implantation of the cardiac synchronization therapy device after randomization [19][20][21][22][23]25,27,28 (Table 2). (For details see Appendix 5, at www.cmaj.ca /cgi /content /full /cmaj .101685 /DC1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were of good to moderate quality. Two trials reported that allocation to treatment group had been concealed (CARE-HF and MIRACLE), blinding occurred in three trials (CONTAK-CD, MUSTIC-SR and MIRACLE) and intention-to-treat was used in four analyses (CARE-HF, COMPANION, MIRACLE and MUSTIC-SR) [8][9][10][11]. In our study only patients who fulfilled criteria for an ICD also got the CRT-D pacemaker according to the guidelines of European Society of Cardiology [12].…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo, el reconocimiento de todos los factores predictores de respuesta clínica favorable y de los mecanismos que influyen en la mejoría de los pacientes, todavía no totalmente conocidos, sería de gran utilidad para refinar la selección de los pacientes que pueden beneficiarse de las técnicas de TRC. Por último, el efecto de este tratamiento en la supervivencia es el gran interrogante que en el futuro debe ser aclarado mediante los estudios multicéntricos actualmente en marcha 22 . En nuestra serie incluimos a 6 pacientes con insuficiencia cardíaca avanzada que ya estaban siendo estimulados crónicamente desde ápex de ventrículo derecho (VD) por bloqueo auriculoventricular completo para quienes no se disponía de otras opciones terapéu-ticas.…”
Section: Discussionunclassified